Suppression of motor protein KIF3C expression inhibits tumor growth and metastasis in breast cancer by inhibiting TGF-β signaling. Issue 1 (1st November 2015) - Wang, Chengqin; Wang, Chenggang; Wei, Zhimin; Li, Yujun; Wang, Wenhong; Li, Xia; Zhao, Jing; Zhou, Xuan; Qu, Xun; Xiang, Fenggang
Highlights: KIF3C over-expressed in breast cancer. High expression of KIF3C was associated with tumor metastasis and recurrence. Silencing of KIF3C suppressed breast cancer cell proliferation and invasion through TGF-β signaling. Abstract: Breast cancer is the most common cause of death among women. KIF3C, a member of kinesin superfamily, functions as a motor protein involved in axonal transport in neuronal cells. To explore the expression, regulation and mechanism of KIF3C in breast cancer, 4 breast cancer cell lines and 93 cases of primary breast cancer and paired adjacent tissues were examined. Immunohistochemistry, Real Time Polymerase Chain Reaction (RT-PCR), Western blot, flow cytometry, short hairpin RNA (shRNA) interference, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), colony formation techniques and xenograft mice model were used. We found that KIF3C was over-expressed in breast cancer tissues and such high KIF3C expression was also associated with tumor recurrence and lymph node metastasis. Silencing of KIF3C by shRNA inhibited epithelial-mesenchymal transition and metastasis by inhibiting TGF-β signaling and suppressed breast cancer cell proliferation through inducing G2 /M phase arrest. The tumor size was smaller and the number of lung metastatic nodules was less in KIF3C depletion MDA-MB-231 cell xenograft mice than in negative control group. These results suggested that high expression of KIF3C in breast cancer may be associated with the tumor progression and metastasis.